Ultrafast electron kinetics in short pulse laser-driven dense hydrogen. (25th September 2015) - Zastrau, U; Sperling, P; Fortmann-Grote, C; Becker, A; Bornath, T; Bredow, R; Döppner, T; Fennel, T; Fletcher, L B; Förster, E; Göde, S; Gregori, G; et al.
Abstract: Dense cryogenic hydrogen is heated by intense femtosecond infrared laser pulses at intensities of W cm −2 . Three-dimensional particle-in-cell (PIC) simulations predict that this heating is limited to the skin depth, causing an inhomogeneously heated outer shell with a cold core and two prominent temperatures of about and for simulated delay times up to after the laser pulse maximum. Experimentally, the time-integrated emitted bremsstrahlung in the spectral range of 8–18 nm was corrected for the wavelength-dependent instrument efficiency. The resulting spectrum cannot be fit with a single temperature bremsstrahlung model, and the best fit is obtained using two temperatures of about 13 and eV. The lower temperatures in the experiment can be explained by missing energy-loss channels in the simulations, as well as the inclusion of hot, non-Maxwellian electrons in the temperature calculation. We resolved the time-scale for laser-heating of hydrogen, and PIC results for laser–matter interaction were successfully tested against the experiment data.